ChemInform Abstract: Synthesis, Crystal Structure and Luminescence Properties of CaY2‐xEuxGe3O10 (x = 0—2). Issue 44 (14th October 2013) - Lipina, Olga A.; Surat, Ludmila L.; Melkozerova, Marina A.; Tyutyunnik, Alexander P.; Leonidov, Ivan I.; Zubkov, Vladimir G.
Abstract The red emitting title phosphors are prepared by solid state reaction of stoichiometric mixtures of Y2O3, Eu2O3, CaCO3, and GeO2 (1250 °C, 72 h) and by an EDTA‐complexing process from nitric acid solutions of Y2O3, Eu2O3, and CaCO3, EDTA, and ammonia solutions of GeO2 (annealing at 1100 °C, 6 h).